Mental and Physical Development of Preschool Children Born After Assisted Reproduction - Tatiana G. Bokhan; Anna V. Silaeva; Svetlana B. Leshchinskaia; Olga V. Terekhina (СибСкрипт, 2023)
This empirical study compared the mental (intellectual, personal, emotional, social) and physical development of four-year-old children conceived by assisted reproduction technology (ART) with that of naturally conceived children. The sample consisted of 90 ART children and 130 spontaneously conceived children (control). The research revealed no significant differences in behavior, emotional development, gender roles, intellectual development (visual-motor coordination, logical thinking, vocabulary, conceptual knowledge, speech development, counting and reading skills), physical development, emotional and behavioral eating habits, and dental health. The ART children demonstrated significantly higher symptoms of social developmental disorders and lower levels of categorizing skills, with a low effect size. The article introduces significant relationships across various components of mental development, as well as between mental and physical development of ART children vs. control. The majority of preschool children conceived by ART had normative development, but the study revealed a risk group and problem areas of development, which require monitoring and early correction.